Downregulation of CYP3A and P-Glycoprotein in the Secondary Inflammatory Response of Mice With Dextran Sulfate Sodium-Induced Colitis and Its Contribution to Cyclosporine A Blood Concentrations - Shoji Kawauchi; Tsutomu Nakamura; Ikuya Miki; Jun Inoue; Tsuneo Hamaguchi; Toshihito Tanahashi; Shigeto Mizuno (Elsevier, 2014)
CYP3A and P-glycoprotein (P-gp) play important roles in drug metabolism and excretion; however, their functions in pathological conditions remain unclear. Hepatobiliary abnormalities have been described in patients with ulcerative colitis, which may affect drug metabolism and excretion in the liver and small intestine. We examined the functions of CYP3A and P-gp in the liver and small intestine of mice with dextran sodium sulfate (DSS)-induced colitis. Up to day 7, inflammatory markers were significantly increased in the livers of DSS-treated mice, accompanied by decreased CYP3A. Additionally hepatobiliary transporters and Pregnane X receptor, which regulates the transcriptional activation of CYP3A, were reduced. Both CYP3A and P-gp were significantly decreased in the upper small intestine of DSS-treated mice on day 7. This was associated with the increased expression of inducible nitric oxide synthase, but not changes in nuclear receptor expression. On day 7 of DSS treatment, the concentrations of cyclosporine A (CsA), a substrate of both CYP3A and P-gp, were significantly higher than controls. These results indicated the existence of a second inflammatory response in the liver and upper small intestine of mice with DSS-induced colitis, and bioavailability of CsA was increased by the dysfunction of CYP3A and P-gp in these organs. [Supplementary Tables and Figure: available only at http://dx.doi.org/10.1254/jphs.13141FP] Keywords:: cyclosporine A, cytochrome P450 3A, dextran sulfate sodium, experimental colitis model, P-glycoprotein